Energy Outage Analysis of Aerial UAV-Enabled SWIPT Deployments - Van Son Nguyen; Tien Hoa Nguyen (IEEE Access, 2024)
This work investigates the energy-outage performance of aerial unmanned aerial vehicles (UAV)-enabled simultaneous wireless information and power transfer (SWIPT) deployments. Focus on the energy preservation challenges for battery-powered UAVs to maintain hovering in the sky, we propose two energy-based antenna approaches, including energy-based single antenna selection (ESAS) and energy-based maximal antenna transmission (EMAT), to improve the energy-outage probability (EOP). In order to evaluate EOP, we derive closed-form approximations for two proposed ESAS and EMAT schemes as well as the asymptotic EOP formulations. In addition, we deduce the system diversity gain, the performance gap between the two proposed schemes, and guidelines for some useful information in system designs. Moreover, we also carry out an optimization of aerial UAV position to minimize the EOP when dealing with certain service areas. Through the Monte-Carlo method, extensive numerical results show that: 1) Simulation results align well with our analytical approximations; 2) For achieving the same EOP requirement, the use of EMAT consumes less than 3 dB of the transmit power compared to ESAS; 3) Compared to ESAS, the adoption of EMAT with more than four antennas at the UAV supply and aerial hovering UAV nodes reduced EOP by more than 100 times; 4) The considered SWIPT-PS mechanism results in a 10 times better EOP improvement than the SWIPT-TS one; and 5) Optimizing the position of aerial hovering UAVs lead to the EOP minimization significantly.